A Systematic Review: Mindfulness Intervention for Cancer-Related Pain - Srisuda Ngamkham; Janean E Holden; Ellen Lavoie Smith (Elsevier, 2019)
Moderate-to-severe pain is a common problem experienced by patients with cancer. Although analgesic drugs are effective, adverse side effects are common and some analgesic drugs are addictive. Nonpharmacological treatment may be a way to treat cancer pain without causing negative side effects. Mindfulness is used as an effective nonpharmacological treatment to improve quality of life (QoL) and to address psychological problems including distress, anxiety, stress, and depression. However, the effect of mindfulness on pain severity has not been sufficiently investigated. Therefore, a systematic review was undertaken to describe the effectiveness of mindfulness interventions for pain and its underlying pathophysiologic mechanisms. The search was conducted in PubMed, Ovid MEDLINE, and CINAHL and included only empirical studies published from 2008 to 2017. Search terms included mindfulness, mindfulness-based intervention, meditation, cancer, pain, and cancer-related pain. Six studies met the search criteria. These studies tested several types of intervention including mindfulness-based stress reduction, mindfulness-based cognitive therapy, meditation with massage, and mindful awareness practices. Study outcomes include improved pain severity, anxiety, stress, depression, and QoL. However, most studies reviewed were conducted in the United States and Denmark. Further research is needed to test culturally appropriate mindfulness interventions to reduce pain.